A new treatment for children with chronic tic disorders – Resource activation. (March 2019) - Viefhaus, Paula; Feldhausen, Marion; Görtz-Dorten, Anja; Volk, Helene; Döpfner, Manfred; Woitecki, Katrin
Highlights: Youth with tics often experience functional impairment and reduced quality of life. During resource activation reductions of tic severity and impairment were shown. Comparing treatment and diagnostic phase, an effect emerged in clinical tic rating. No significant improvement was found regarding comorbid problems and self-esteem. Resource activation may be an alternative treatment for some youth with tics. Abstract: The aim of this pilot study is to evaluate the efficacy of a resource activation (RA) program as an alternative intervention for children and adolescents with tic disorders. RA interventions focus on the strengths and abilities of the patients. This is expected to improve the patients' perceptions regarding their own resources, which may indirectly result in a reduction of tic symptoms, impairment and comorbid conditions. A within-subject design with two phases (8 weeks diagnostic; 16 sessions treatment) was analyzed using multilevel modeling ( n = 24). During the treatment phase, significant reductions of tics were found in clinical rating (Yale Global Tic Severity Scale; YGTSS), parent rating and video observation (motor tics). Moreover, an improvement was shown on most tic-related impairment and subjective burden (SB) ratings. No significant improvement was found regarding comorbid problems and self-esteem. Compared to the preceding diagnostic phase, a significant incremental treatment effect emerged in clinical rating of tic symptoms (YGTSS) and video observation (motor tics). This pilot study provides first hints that RA may represent an effective treatment for reducing tic symptoms, impairment and SB. However, further research is needed in order to establish RA as an effective treatment for tic disorders.